A qualitative study of diphenhydramine injection in Kyrgyz prisons and implications for harm reduction - Jaimie P. Meyer; Gabriel J. Culbert; Lyuba Azbel; Chethan Bachireddy; Ainura Kurmanalieva; Tim Rhodes; Frederick L. Altice (BMC, 2020)
Abstract Background To reduce opioid dependence and HIV transmission, Kyrgyzstan has introduced methadone maintenance therapy and needle/syringe programs into prisons. Illicit injection of diphenhydramine, an antihistamine branded as Dimedrol®, has been anecdotally reported as a potential challenge to harm reduction efforts in prisons but has not been studied systematically. Methods We conducted qualitative interviews in Kyrgyz or Russian with prisoners (n = 49), former prisoners (n = 19), and stakeholders (n = 18), including prison administrators and prisoner advocates near Bishkek, Kyrgyzstan from October 2016 to September 2018. Interviews explored social-contextual factors influencing methadone utilization in prisons. Transcripts were coded by five researchers using content analysis. Dimedrol injection emerged as an important topic, prompting a dedicated analysis. Results After drinking methadone, some people in prison inject crushed Dimedrol tablets, a non-prescription antihistamine that is banned but obtainable in prison, to achieve a state of euphoria. From the perspectives of the study participants, Dimedrol injection was associated with devastating physical and mental health consequences, including psychosis and skin infections. Moreover, the visible wounds of Dimedrol injecting contributed to the perception of methadone as a harmful drug and supporting preference for heroin over methadone. Conclusion Dimedrol injecting is a potentially serious threat to harm reduction and HIV prevention efforts in Kyrgyzstan and elsewhere in the Eastern European and Central Asian region and requires further investigation.